AVALIAÇÃO DO DESEMPENHO DE CONCRETOS COM ADIÇÕES MINERAIS QUANTO À CORROSÃO DAS ARMADURAS INDUZIDA POR CLORETOS - OLIVEIRA, Andrielli Morais de (2007)
The present work aims to study the performance of concrete with regard to the action of chloride ions, evaluating the influence of both mineral additions and water/binder ratio (w/b), considering kinetic and thermodynamic aspects of the corrosive phenomenon. A experimental research was carried out considering the following variables: the presence of mineral additions in partial substitution to the cement weight (10% of silica fume; 25% of fly ash; 10%, 20% and 30% of metakaolin) and the water/binder ratio (0,40 and 0,55). Thus, cubic concrete test specimens were produced, in addition to cylindrical test specimens for concrete characterization in relation to the compressive strength, specific mass, void ratio and capillary water absorption. After 645 days of casting, the cubic concrete test specimens were submitted to the chlorides attack during 308 days, totality 44 weekly cycles of immersion in chlorides aggressive solution. They were monitored, throughout this period, by means of techniques, such as: the concrete electric resistivity, the half-cell potential, the polarization resistance and the electrochemical impedance spectroscopy. At the end of the experiment, visual inspections of reinforcing steels allowed to observe their superficial aspects after attack. As general result, it was gotten that the incorporation of mineral additions to the concretes promoted significant profits in all the evaluated properties, evidencing the beneficial effect of these additions in concretes exposed to aggressive conditions, specially in those in which there are chloride ions. In this direction, the statistical analysis has shown evidences that concretes with silica fume and metakaolin achieved the best results of electrical resistivity. In relation to the half-cell potentials, the reference concrete (without mineral additions) presented the worst performance, with an indication of despassivation in the reinforcing steels accentuated fall in the values of resistance of polarization with the time, proving the susceptibility of these systems to the action of chlorides. The concrete with mineral additions did not present depassivation of the reinforcing steels meaning that these systems possess great durability and service life in relation to those without mineral additions